Obesity, but not metabolic syndrome, negatively affects outcome in bipolar disorder. (26th June 2015) - McElroy, S. L.; Kemp, D. E.; Friedman, E. S.; Reilly‐Harrington, N. A.; Sylvia, L. G.; Calabrese, J. R.; Rabideau, D. J.; Ketter, T. A.; Thase, M. E.; Singh, V.; Tohen, M.; Bowden, C. L.; et al.
Abstract : Objective: Examine the effects of obesity and metabolic syndrome on outcome in bipolar disorder. Method: The Comparative Effectiveness of a Second Generation Antipsychotic Mood Stabilizer and a Classic Mood Stabilizer for Bipolar Disorder (Bipolar CHOICE) study randomized 482 participants with bipolar disorder in a 6‐month trial comparing lithium‐ and quetiapine‐based treatment. Baseline variables were compared between groups with and without obesity, with and without abdominal obesity, and with and without metabolic syndrome respectively. The effects of baseline obesity, abdominal obesity, and metabolic syndrome on outcomes were examined using mixed effects linear regression models. Results: At baseline, 44.4% of participants had obesity, 48.0% had abdominal obesity, and 27.3% had metabolic syndrome; neither obesity, nor abdominal obesity, nor metabolic syndrome were associated with increased global severity, mood symptoms, or suicidality, or with poorer functioning or life satisfaction. Treatment groups did not differ on prevalence of obesity, abdominal obesity, or metabolic syndrome. By contrast, among the entire cohort, obesity was associated with less global improvement and less improvement in total mood and depressive symptoms, suicidality, functioning, and life satisfaction after 6 months of treatment. Abdominal obesity was associated with similar findings. Metabolic syndrome had no effect on outcome. Conclusion: Obesity and abdominal obesity, but not metabolic syndrome, were associated with less improvement after 6 months of lithium‐ or quetiapine‐based treatment.